Association of Apolipoprotein E gene polymorphism with Preeclampsia: a meta-analysis. (2nd April 2020) - Abyadeh, Morteza; Heydarinejad, Fatemeh; Khakpash, Maliheh; Asefi, Yaser; Shab-Bidar, Sakineh
ABSTRACT: Objective: The aim of this meta-analysis was to examine the association of ApoE polymorphism with the risk of developing PE. Methods: A comprehensive search was carried out through PubMed, Scopus, and Embase. The ORs with corresponding 95% CIs were extracted. Fixed model was used for meta-analysis and in case of existing heterogeneity a random-effects model was applied. Results: Association of ApoE polymorphism with the risk of developing PE was not statistically significant (OR = 0.86, 95% CI: 0.67–1.11; OR = 0.92, 95%CI: 0.73–1.15, respectively for ε2 and ε4). Conclusion: ApoE polymorphism might not be associated with the risk of PE.